PENGEMBANGAN GAME EDUKASI BERBASIS WEB SCRATCH UNTUK MANAJEMEN PERILAKU SOSIAL PADA ANAK AUTIS - Madeline Pinky Aagustin; Ratu Panduwinata; Angelia Destaratih Magriszka; Wiwik Widajati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses the development of a web-based educational game scratch as a tool for managing social skills in autistic children. This application is designed to help children practice improving social skills through interactive and interesting media with a focus on improving social interaction, communication and adaptive behavior. This study uses a Research and Development (R&D) approach by adopting the ADDIE development model. And using a validation test method carried out by experts in their fields. The results of the validation test showed that the web-based educational game scratch obtained a feasibility level of 89% with the conversion results against the percentage indicator criteria indicating that this learning media is included in the category of very feasible for use in the social skills learning process.